3D plum candy-like NiCoMnO4@graphene as anodes for high-performance lithium-ion batteries. Issue 74 (19th December 2018) - Tao, Jianming; Liu, Guozhen; Chen, Yuhan; Chi, Yubin; Hong, Lixun; Lin, Zhiya; Lin, Yingbin; Huang, Zhigao
Abstract : 3D plum candy-like NiCoMnO4 microspheres have been prepared via ultrasonic spraying and subsequently wrapped by graphene through electrostatic self-assembly. Abstract : 3D plum candy-like NiCoMnO4 microspheres have been prepared via ultrasonic spraying and subsequently wrapped by graphene through electrostatic self-assembly. The as-prepared NiCoMnO4 powders show hollow structures and NiCoMnO4 @graphene exhibits excellent electrochemical performances in terms of rate performance and cycling stability, achieving a high reversible capacity of 844.6 mA h g −1 at a current density of 2000 mA g −1 . After 50 cycles at 1000 mA g −1, NiCoMnO4 @graphene delivers a reversible capacity of 1045.1 mA h g −1 while the pristine NiCoMnO4 only has a capacity of 143.4 mA h g −1 . The hierarchical porous structure helps to facilitate electron transfer and Li-ion kinetic diffusion by shortening the Li-ion diffusion length, accommodating the mechanical stress and volume change during the Li-ion insertion/extraction processes. Analysis from the electrochemical performances reveals that the enhanced performances could be also attributed to the reduced charge-transfer resistance and enhanced Li-ion diffusion kinetics because of the graphene-coating. Moreover, Schottky electric field, due to the difference in work function between graphene and NiCoMnO4, might be favorable for the redox activity of the NiCoMnO4 . In light of the excellent electrochemical performance and simple preparation, we believe that 3D plum candy-like NiCoMnO4 @graphene composites are expected to be applied as a promising anode materials for high-performance lithium ion batteries.